Results of a Randomized, Double-Blinded, Placebo-Controlled, Phase 2.5 Study of Saracatinib (AZD0530), in Patients with Recurrent Osteosarcoma Localized to the Lung. (1st May 2020) - Baird, Kristin; Glod, John; Steinberg, Seth M.; Reinke, Denise; Pressey, Joseph G.; Mascarenhas, Leo; Federman, Noah; Marina, Neyssa; Chawla, Sant; Lagmay, Joanne P.; Goldberg, John; Milhem, Mohammed; et al.
Abstract : Purpose . Osteosarcoma is a rare cancer and a third of patients who have completed primary treatment will develop osteosarcoma recurrence. The Src pathway has been implicated in the metastatic behavior of osteosarcoma; about 95% of samples examined express Src or have evidence of downstream activation of this pathway. Saracatinib (AZD0530) is a potent and selective Src kinase inhibitor that was evaluated in adults in Phase 1 studies. The primary goal of this study was to determine if treatment with saracatinib could increase progression-free survival (PFS) for patients who have undergone complete resection of osteosarcoma lung metastases in a double-blinded, placebo-controlled trial. Patients and Methods . Subjects with recurrent osteosarcoma localized to lung and who had complete surgical removal of all lung nodules were randomized within six weeks after complete surgical resection. Saracatinib, or placebo, was administered at a dose of 175 mg orally, once daily, for up to thirteen 28-day cycles. Results . Thirty-seven subjects were included in the analyses; 18 subjects were randomized to receive saracatinib and 19 to receive placebo. Intent-to-treat analysis demonstrated a median PFS of 19.4 months in the saracatinib treatment group and 8.6 months in the placebo treatment group (p = 0.47 ). Median OS was not reached in either arm. Conclusions . Although saracatinib was well tolerated in this patient population, there was no apparent impact of the drug in this double-blinded, placebo-controlled trial on OS, and Src inhibition alone may not be sufficient to suppress metastatic progression in osteosarcoma. There is a suggestion of potential clinical benefit as evidenced by longer PFS in patients randomized to saracatinib based on limited numbers of patients treated.